2018
DOI: 10.1055/s-0043-121628
|View full text |Cite
|
Sign up to set email alerts
|

Novel Demonstration of the Anterior Femoral Cutaneous Nerves using Ultrasound

Abstract: This study confirms that the IFCN and the MFCN can be reliably visualized with HRUS throughout the course of these nerves, both in anatomical specimens and in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 21 publications
2
25
0
2
Order By: Relevance
“…The dissections in this study showed that the IFCN branches can be identified where they pierce the FL using ultrasound with a 100% success rate of correct identification. The observed pattern with the IFCN dividing into two main branches corresponds to the findings by Pivec et al , who targeted the IFCN at the point of origin from the FN, at the midportion of the thigh and at the most distally visible point 14. In this study, the level of injection was at the level where the IFCN branches pierce the FL, approximately 10 cm below the intersection of the inguinal crease and the FA (9.6 cm (SD 1.4)).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The dissections in this study showed that the IFCN branches can be identified where they pierce the FL using ultrasound with a 100% success rate of correct identification. The observed pattern with the IFCN dividing into two main branches corresponds to the findings by Pivec et al , who targeted the IFCN at the point of origin from the FN, at the midportion of the thigh and at the most distally visible point 14. In this study, the level of injection was at the level where the IFCN branches pierce the FL, approximately 10 cm below the intersection of the inguinal crease and the FA (9.6 cm (SD 1.4)).…”
Section: Discussionsupporting
confidence: 86%
“…The IFCN branches pierce the fascia lata (FL) and become subcutaneous in the proximal part of the FT (figure 1). 13–17 See online supplementary appendix 1 for a detailed review of the nomenclature and anatomy of the AFCN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The medial branch descends obliquely along the sartorius muscle, pierces the fascia lata at the distal third of the thigh, and provides cutaneous sensation to the medial aspect of the thigh. Both branches may have an anastomosis with the lateral femoral cutaneous nerve, the infrapatellar branch of the saphenous nerve, and the obturator nerve to form the subsartorial plexus ( Figure 8 A) [ 28 ].…”
Section: The Anterior Femoral Cutaneous Nerve (Afcn)mentioning
confidence: 99%
“…Die Sonografie ist die Methode der Wahl für die Bildgebung des peripheren Nervensystems [1]. Klinisch ist die Darstellung insbesondere der kleinen peripheren Nerven für folgende Anwendungen relevant: (i) ihre Lokalisierung, um Schäden während chirurgischer oder anderer invasiver Eingriffe zu vermeiden [2][3][4], (ii) die Zielführung applizierbarer Therapeutika oder chirurgischer Eingriffe an diesen Nerven [5][6][7][8][9], und (iii) zur Bestimmung ihres Kalibers für die Beurteilung von kompressiven, entzündlichen oder degenerativen Neuropathien [12][13][14][15][16][17][18].…”
unclassified